Системная склеродермия у детей: два клинических случая - Подлианова, Е. И.; Подліанова, Олена Іванівна; Podlianova, E. I. (Полтава: УМСА, 2015)
В статье изложены современные данные про клинические проявления и диагностику системной склеродермии. Описаны два клинических случая ювенильной формы системной склеродермии, представляющие два варианта течения и активности патологического процесса. Учитывая редкую встречаемость патологии у детей, сложность диагностики, описанные примеры будут полезны врачам различных специальностей. У статті викладені сучасні дані про клінічні прояви та діагностику системної склеродермії. Описано два клінічних випадка ювенільної форми системної склеродермії, що представляють два варіанти перебігу та активності патологічного процесу. Враховуючи не високу розповсюдженість патології у дітей, складність діагностики, описані приклади будуть корисні лікарям різних спеціальностей. Systemic sclerosis (SS) is a progressive disease with polisyndrom characteristic changes in the skin, locomotor system, internal organs and widespread violations of the type of vasospastic Raynaud’s phenomenon. It is assumed there is multifactorial genesis of pathology due to the interaction of adverse exogenous and endogenous factors with a genetic predisposition to the disease. In the pathogenesis of SS the key role is played by impaired immunity, leading to the increase in collagen and fibroformations, changes in the microcirculation with the activation and proliferation of endothelial and smooth muscle cells, obliterating the development of microangiopathy. This in turn leads to a further activation of the immune system and fibroblasts that vicious circle of disease progression. From 5 clinical forms of SS in pediatrics the most common is with juvenile onset before 16 years of age, focal lesions of skin and gemiforms, erased by Raynaud’s phenomenon, articular syndrome with the development of contractures, the formation of abnormal development of limbs, unexpressed visceral pathology. They distinguish acute, subacute and chronic course; three stages and the degree of disease activity. To put the diagnosis of juvenile SS for the patient under the age of 16 the presence of proximal scleroderma and two small signs of the following are obligatory: sclerodactyly, Raynaud’s phenomenon, digital tip ulcers, dysphagia, gastroesophageal reflux, arrhythmias, pulmonary fibrosis et al. Serological markers of autoimmunity play the important role here too: antinuclear antibodies, sc-selective autoantibodies (anticentromere, anti–topoisomerase I [Scl-70], antifibrillarin, anti–PM-Scl, antifibrillin or anti–RNA polymerase I or III). In children, the true frequency of SS is not known. In Zaporozhye 4 children with the diagnosis of SS are currently registered. Despite the fact that in medical literature there are a lot of publishedworks on the SS, the diagnosis of this illness in children continues to cause difficulties for doctors-practitioners. Therefore we are presenting to our readers the two clinical cases of SS in children. The first example is the story of the boy’s (M., 8 years old) illness. He appealed with the complains of pain in his right heel while walking, reduced size and deformation of thethird finger on his right foot, redness and hyper pigmentation of round and linear form on the foot. As the result of the examination the diagnosis is the following: Systemic scleroderma, juvenile form, a chronic course, the initial stage, 1 degree activity. Noteworthy that the serological autoimmune markers were negative. During the therapy he received antifibrotic, cardiovascular, anti-inflammatory drugs, disaggregants, local treatment. The second example -a girl, O., 8 years old. Complaints againstmultiple focal changes in the skin in the form of seals, areas of hypo- and hyperpigmentation, keratosis, dense edema, skin elasticity, scarring, moderate muscle-tendon contracture in the interphalangeal joints of the hands, feet, wrist joints. The chest radiograph shows local fibrosis S10on both sides. She is being monitored for 5 years with the diagnosis of Systemic scleroderma, juvenile form, diffuse lesion of the skin, joints syndrome, Raynaud’s phenomenonerased, focalfibrosis (S10) on both sides, reactive hepatitis, subacute course. During the entire observation period the increased rates of autoimmune markers are preserved: total antibodies to DNA 3-4 times higher and total antinuclear antibodies by 5-6 times. In contrast to the first patient, the girl’s treatment includes corticosteroids and immunosuppressants. The presented cases of juvenile SS are indicative. They represent the two variants of the pathological process activity and flow. Taking into consideration the rare occurrence of SS in children and the complexity of the diagnosis the described examples will be useful for doctors of various specialties.
Системна склеродермія у дітей: два клінічні випадки
Systemic Sclerosis in Children: Two Clinical Cases
Keywords: ювенильная системная склеродермия; дети; ювенільна системна склеродермія; діти; juvenile systemic sclerosis; children